Modelling of the energy metabolism in cyclist using ergometer tests - Weber, S.; Platen, P. (International Journal of Computer Science in Sport, 2002)
In competitive cycling the available power and therefore available energy has a great influence on the overall performance in competition. Therefore the diagnostic of the energy metabolism in cycling sports has become a major field in theoretical and applied sport science. With the common performance tests, it is impossible to evaluate the metabolic background causing a specific physiological reply to a load applied to the system.